Internal Model Control Scheme-Based Voltage and Current Mode Control of DC–DC Boost Converter - Purnima Verma (17949263) (2023)
In this work, a current mode control has been proposed for output voltage regulation of DC–DC boost converter. The proposed controller has a cascade control structure with two feedback loops. And the internal model control scheme has been used in both the control loops. The advantageous feature lies in so as to adjust the performance and robustness of the closed-loop system as it has only one tuning parameter. The performance of the proposed internal model control based current mode control of DC–DC boost converter has been evaluated in hardware setup for set point as well as load disturbance response. The load disturbance response has been analyzed by considering random changes in input voltage and load. The faster transient response with a low-rise time and settling time has been observed in the proposed current mode control in comparison with voltage mode control as well as recently reported work. The robustness analysis of the proposed schemes has also been conducted using the small gain theorem and is further validated through hardware experiment. The proposed scheme is robustly stable up to 23% simultaneous change in inductance, capacitance and resistance. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2023.3320272